Spectrometric Microfluidic Technique for Determination of Mercury (II) in Water Using Dithizone as Chromogenic Reagent - K. Mousah, Rasha; S. Zageer, Dheaa; A. Kasar, Khawla (Al-Nahrain Journal of Science, 2025)
Mercury is an extremely toxic metal that causes many health problems for Organisms even if it is present in small concentrations. There for It is necessary to detect its levels in water, manage and control mercury levels in water with a simple and fast analytical device there for this paper present a class of microfluidic devices, which is locally manufactured. Microfluidic chip made of PMMA emerged with dithizon,e which was used as a chromogenic agent with high sensitivity for low concentration of the metal ion, the method enhanced with colorimetric analysis using image J software.